Causal factors of digital marketing, market orientation, and entrepreneurial personality affecting the performance of hormone therapy business - Amnajcharoensak, Thanate; Paopun, Natsapun (Edelweiss Applied Science and Technology, 2025)
Currently, health products, especially hormone therapy products designed to enhance male sexual performance, are attracting growing attention as solutions to various health concerns. However, the development of these products is challenged by the lack of detailed consumer demographic data in this niche market. The objectives of this study were: 1) to examine the causal factors of digital marketing, market orientation, and entrepreneurial personality affecting the performance of the hormone therapy business, 2) to investigate the influence of causal factors of digital marketing, market orientation, and entrepreneurial personality on hormone therapy business performance, and 3) to develop marketing strategies based on the causal factors of digital marketing, market orientation, and entrepreneurial personality affecting the performance of the hormone therapy business. The researcher collected data through interviews and online questionnaires targeting male subjects between March and April 2025, with a sample size of 360 respondents. The analysis results indicate that digital marketing, market orientation, and entrepreneurial personality had a strong and positive relationship with business performance. Therefore, digital marketing, market orientation, and entrepreneurial personality played a meaningful and direct role in driving business success in this growing health product category.